Power in the Pandemic: The UK Government's Discursive Control of the Population - Norman, Isabelle (2022)
As COVID-19 took hold of the UK, and the world, the UK Government were faced with the complicated challenge of protecting society. Within a system of biopolitical governmentality, the population is controlled not simply through the implementation of explicit rules and laws (although the pandemic saw plenty of these), rather it is directed towards self-governance through mechanisms of conduct of conduct. While the UK has not yet escaped the grip of COVID-19, much literature has nonetheless emerged in its wake already. As lockdown measures were implemented, there was a growing concern that the pandemic was facilitating governmental overreach (Agamben, 2020[a]; Denisenko & Trikoz, 2020; Santis, 2020; Zinn, 2020). Equally important, however, are the implicit tactics used by the government to exert control over the population by shaping the fabric of society. This study found that the Government’s constructions of the roles of science, the Government, the people, and the virus formed an integrated discourse that worked to protect the Government’s position of power and manage the population. The construction of science was employed to protect the Government from a virus with agency outside of the reach of state power, and from the implications of prioritising the economy over the people.